Occurrence of Brucella ovis infection in sheep of the municipality of Alegre/ES - Botelho, Samuel; Rodrigues Zeferino, Macllene; Cogo Clipes, Renata; Barioni, Graziela; Molinari Donatele, Dirlei; Camilato Lima Costa, Leonardo (Pubvet, 2018)
The objective of the present study was investigate the prevalence of infection by Brucella ovis in flocks of sheep in the city of Alegre, located in southern Espirito Santo, Brazil. The infection mainly affects the reproductive tract of infected animals, causing epididymitis, orchitis with compromised sperm quality in males as well as abortion and weak and premature lambs in pregnant females, and endometritis in empty females. Three properties were visited, totalizing 197 animals, where blood samples were collected and subsequently centrifuged to investigate the presence of antibodies against B. ovis by IDGA. From those animals, 20 (10.15%) were positive. In this way, it was observed the first serological evidence of infection by B. ovis in flocks of sheep at Alegre/ES, which can lead to compromised productivity of the herd, being used to control the spread of infection to healthy animals.
Keywords: epidemiology; orchitis; ovine brucellosis